2008
DOI: 10.3168/jds.2007-0057
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Lusitano Mare Lactation Curve with Wood's Model

Abstract: Milk yield and composition data from 7 nursing Lusitano mares (450 to 580 kg of body weight and 2 to 9 parities) were used in this study (5 measurements per mare for milk yield and 8 measurements for composition). Wood's lactation model was used to describe milk fat, protein, and lactose lactation curves. Mean values for the concentration of major milk components across the lactation period (180 d) were 5.9 g/kg of fat, 18.4 g/ kg of protein, and 60.8 g/kg of lactose. Milk fat and protein (g/kg) decreased and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
25
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 23 publications
17
25
1
1
Order By: Relevance
“…the increasing or the decreasing of the values during the lactation, are in agreement with those reported in literature (Santos and Silvestre 2008;Centoducati et al 2012).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…the increasing or the decreasing of the values during the lactation, are in agreement with those reported in literature (Santos and Silvestre 2008;Centoducati et al 2012).…”
Section: Resultssupporting
confidence: 93%
“…The lactose content observed in colostrum was 4.02 g/100 g. In milk samples it significantly increased, reaching the highest value at 150 days. Similar trends in lactation of 150 days were recorded in Murgese breed (Caroprese et al 2007), in Lusitano breed (Santos and Silvestre 2008), in Heavy Draft breed (Centoducati et al 2012), and in Polish breed (Markiewicz-Keszycka et al 2013). The value of pH was 6.69 in colostrum, and it changed significantly during lactation (P < 0.001): the value observed at 15 days (6.85) was significantly lower than those observed at 90 and 150 days.…”
Section: Resultssupporting
confidence: 79%
“…Lactose content and dry matter resulted significantly the lowest in summer only at 30 days. In the other periods, lactose was not influenced by the considered factors, as reported in literature (Oftedal and Jenness 1988;Santos and Silvestre 2008); dry matter content was in agreement with values reported in the literature for equine milk (Malacarne et al 2002;Miranda et al 2004);Ivanković et al (2009) observed in Croat jenny values that ranged from 8.61 to 9.13 %. Titratable acidity (SH ) resulted highest in summer lactation at 90 and at 150 days, value lower than in cow's milk, attributable to the low content in casein and in phosphate (D'Auria et al 2005;Guo et al 2007).…”
Section: Qualitative Characteristics Of Jenny Milksupporting
confidence: 78%
“…The groups showed a milk production trend similar to that observed in literature by other authors (Giosuè et al 2008;Santos and Silvestre 2008). Milk production, protein, ash, SCS and pH resulted highest in summer at 30 days; protein and pH resulted highest in summer also at 90 and 150 days, respectively (Table 1).…”
Section: Qualitative Characteristics Of Jenny Milksupporting
confidence: 75%
“…Basal lower glucose concentrations in early lactation were also observed in Thoroughbred and Lipizzaner mares when compared with values found in late gestation (Hoffman et al, 2003;Heidler et al, 2004). It is likely that the increased use of glucose during early lactation was influenced by mammary gland demands for lactose synthesis in milk, because mares' milk is highly concentrated in this disaccharide (Doreau et al, 1993;Santos and Silvestre, 2008). The observed decrease on glucose concentrations from spring to summer months and the steady levels found during this season probably reflect the influence of pasture quality and availability, when the nutritional requirements linked to the lactation stage are still important.…”
Section: Blood Metabolitesmentioning
confidence: 82%